Penerapan Tindak Pidana Rehabilitasi Dalam Tindak Pidana Narkotika (Studi Putusan Pengadilan Negeri Jakarta Barat Nomor 582/Pid.Sus/2021/PN Jakarta Barat) - Fitri Ayulia Arfai; Julianus Edwin Latupeirissa; Steven Makaruku (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT : As stated in Article 127 paragraph (3) of Law No. 35 of 2009 concerning Narcotics, abusers or victims of narcotics abuse must receive both medical and social rehabilitation. However, this was stated in the decision of the West Jakarta District Court Number 582/Pid.Sus/2021/West Jakarta PN. In fact, drug abusers or survivors of narcotics are given prison sentences, making it easier to conduct research. The methodology used in this research is normative juridical with considerations of laws and regulations, conceptual considerations and content considerations. The legal materials used are primary, secondary and tertiary legal materials which are analyzed qualitatively. The research results show that rehabilitation is necessary for those who use or possess drugs because they are physically unwell and need to be treated for their addiction. This is in accordance with Article 54 of Law Number 35 of 2009 concerning Narcotics. Sentence of imprisonment for 5 months in the decision of the West Jakarta District Court Number 582/Pid.Sus/2021/PN Jakarta Barat. Has fulfilled the elements in Article 127 paragraph (1), but will refer to the principle of restorative justice that imposing a sentence on narcotics addicts is inappropriate because it is not oriented towards recovery but rather oriented towards retaliation.